Abdominal trauma sustained during cardiopulmonary resuscitation may be detected by ultrasound. (October 2016) - Graham, Blair; Nutbeam, Tim; Smith, Jason E
Cardiopulmonary resuscitation is a potentially lifesaving intervention, although significant iatrogenic injury may occur. Unlike cardiac and thoracic injuries, the incidence of abdominal injuries as a consequence of cardiopulmonary resuscitation has not been defined. We report a case of significant abdominal injury sustained during cardiopulmonary resuscitation, which was incidentally detected using focussed ultrasound. A review of the available literature summarises the incidence of abdominal injuries sustained during cardiopulmonary resuscitation. We consider whether the standard application of focussed abdominal ultrasound is desirable as part of post-resuscitation care. Clinicians should consider the potential for iatrogenic injuries following resuscitation, especially where persistent and unexplained haemodynamic instability occurs following return of spontaneous circulation. Many emergency departments have access to point-of-care ultrasound and staff skilled in focussed assessment with sonography for trauma. Post-resuscitation detection of abdominal injuries could be facilitated by utilising this approach. This may improve outcomes for patients with potentially treatable injuries that may have otherwise been missed or diagnosed late.